Factors Affecting Labor Productivity of Small Manufacturing Industry - Mohammad Rizal; Sulton Sholehuddin (University of Merdeka Malang, 2019)
The industrial sector is one of the sources of income in Indonesia, although basically the state of industry in Indonesia still has many problems including regarding low-educated labor, limited capital and uneven income distribution. Malang City is one of region in East Java with a largest source of income from the manufacturing industry sector. The variables observed in this study are education and gender issues on productivity. This study uses primary data obtained through questionnaires and analyzed by multiple regression models. The results show that: 1) Education influences the labor productivity of small-scale manufacturing industries in Malang City; 2) Gender has a positive and significant effect towards labor productivity in small-scale manufacturing industries in Malang City; 3) Male labor productivity is higher than female labor productivity.https://doi.org/10.26905/jmdk.v7i1.2691